The Recent Report on Schiff Bases and their Complexes as DNA Binders - Mansi; Bhutani, Charu; Khanna, Pankaj; Jain, Manisha; Talwar, Sangeeta; Yadav, Shilpa; Khanna, Leena (Current Organic Chemistry, 2023)
Schiff bases are dynamic organic compounds of bioactive importance, acting as flexible ligands and can form complexes with metals. Schiff bases along with their metal complexes have shown a large affinity towards DNA, which is one of the main targets of chemotherapeutics. DNA can join hands with these motifs in multiple ways, like covalent (crosslinking adducts) and non-covalent (intercalative or groove binding via electrostatic) interactions. Besides, the binding ability and types vary with the metals involved in Schiff base metal complexes. Thus, this review aims to describe significant recent reports of Schiff bases and their metal complexes capable of binding with DNA to evaluate the superlative DNA binders, type of association, and best metal-Schiff base combinations. Among the experimental techniques employed in revealing these interactions, noteworthy UV absorption and fluorescence spectroscopy studies have been discussed for the assessment of various types of bindings as intercalation or groove type.
Keywords: groove binding